2019
DOI: 10.3390/admsci9010015
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management as a Success Factor in the International Activity of Spanish Engineering

Abstract: During the period between 2008-2013, the internal market in Spain was characterized by economic crisis, the contraction of the demand experienced in a turbulent business environment, and strong competition among companies. This situation forced many of these companies to work abroad. One of the success factors for Spanish engineering companies abroad has been effective risk management, which avoids compromising the company's objectives, market share, or survival. This article examines the importance of risk ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 80 publications
0
11
1
Order By: Relevance
“…It is notable however that there are some differences found in our findings compared to similar studies in the literature. Specifically, competencies such as technical skills (Murch 2001), financial management (Michalski et al 2018), organizational governance (Kalodimos 2017) and risk management (García-Piqueres et al 2019;Lozano-Torró et al 2019; Klakegg 2016) were ranked as very relevant for effective PM. These disparities are understandable since these studies were conducted in contexts different from ours (DCs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is notable however that there are some differences found in our findings compared to similar studies in the literature. Specifically, competencies such as technical skills (Murch 2001), financial management (Michalski et al 2018), organizational governance (Kalodimos 2017) and risk management (García-Piqueres et al 2019;Lozano-Torró et al 2019; Klakegg 2016) were ranked as very relevant for effective PM. These disparities are understandable since these studies were conducted in contexts different from ours (DCs).…”
Section: Resultsmentioning
confidence: 99%
“…He stressed that it even becomes more relevant when managing construction projects, because these kinds of projects are usually more technical and complex in nature; requiring enough engineering knowledge and the application of scientific principles. Nonetheless, on a relatively different note, other authors have suggested competencies such as financial management (Michalski et al 2018), organizational governance (Kalodimos 2017) and risk management (García-Piqueres et al 2019;Lozano-Torró et al 2019; Klakegg 2016) as relevant for effective PM.…”
Section: Key Competencies For Effective Project Managementmentioning
confidence: 99%
“…One of the significant questions within the scientific debate is risk culture and risk-awareness as they are both providing a positive input to the success and sustainability of the organization. The evidence was proven by several researchers [7][8][9].…”
Section: Questionnaire About Risk-awarenessmentioning
confidence: 87%
“…Compared with the national market, international projects involve more risks, because they take place in environments characterized by political, economic, social, legal and cultural differences that will affect the performance of engineering companies (Lozano-Torr o et al, 2019). With the increasing attention to noncompliance in the construction industry (Le et al, 2014;Owusu et al, 2019;Yap et al, 2020), this study developed a theoretical model to study how the host country's institutional environments affects the PCRs of international contractors with different degrees/ levels of AC.…”
Section: Discussionmentioning
confidence: 99%